PENERAPAN TUJUH DIMENSI PEMASARAN DALAM ENTREPRENEUR MARKETING DI INDONESIA - AMIRUDIN, ROBBY EMMANUEL (Kajian Ilmiah Mahasiswa Manajemen, 2012)
Entrepreneurs are marketing functions of the organization and set of processes for creating, communicating and delivering value to customers and for managing customer relationships in ways that benefit the organization and its stakeholders, and are characterized by innovation, proactive risk taking, and may be done without the current resource controlled. Marketing entrepreneurs have seven dimensions such as innovativeness, proactiveness, opportunity focus, resource leveraging, calculated risk taking, customer intensity and value creation. This paper aims to discuss the implementation of the seven dimensions of marketing in entrepreneur marketing in Indonesia by using examples and discussion of the perfume Bask and Boutique Hotel. The results of this paper is in terms of entrepreneur marketing concepts and techniques can be a solution for marketers to persuade, acquire and retain customers. Entrepreneur marketing can also adjust the dynamic change of environment